From Digital Literacy to Computational Thinking in Economics Education: The Mediating Role of Self-Regulated Learning - Dalughu, Deitawati; Disman; Susanti Kurniawati; Leni Permana (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to examine the effect of digital literacy (DL) on students’ computational thinking (CT) in Economics Education, with self-regulated learning (SRL) serving as a key explanatory factor. A quantitative explanatory survey design was employed with 210 junior high school students from North Sulawesi and Central Kalimantan, Indonesia, who were selected through proportional sampling. Data were collected using Likert-scale questionnaires measuring DL, SRL, and CT and were analyzed using descriptive statistics and univariate linear regression. The results showed that DL significantly predicted SRL (β = 0.75, p < .001) and CT (β = 0.71, p < .001), while SRL significantly predicted CT (β = 0.76, p < .001). The significant direct relationship between DL and CT, together with the significant relationships between DL and SRL and between SRL and CT, suggests that SRL may play an explanatory role in the relationship between DL and CT. Because the direct relationship between DL and CT remained significant, the relationship was not fully accounted for by SRL. These findings highlight the importance of integrating digital literacy with SRL strategies, including goal setting, learning monitoring, strategy use, and self-evaluation, to support the development of students’ computational thinking skills in Economics Education.